The relationship of egypt with arab countries of 1980-1990th year’s - Жaнaтaевa К. Б. (Journal of Oriental Studies, 2017)
This article discusses the reasons for the decline of the mighty Ottoman Empire. The Ottoman Empire collapsed due to a number of reasons. It all started with a big defeat Osman at the walls of Vienna. Decline of the Ottoman Empire began in 1683, when was made the second and the last unsuccessful attempt to conquer Vienna. The Ottoman Empire lost its momentum in its development, and slowly began to fade. Great Empire killed herself, step by step, consistently destroying all the foundations on which rested -economic, social, political, ideological and military. The main reason for the collapse of the Ottoman Empire, is defeated in the First World War.